Crack-healing behaviour of MoSi2 dispersed Yb2Si2O7 environmental barrier coatings. Issue 20 (15th October 2022) - Yuan, Mingjian; Liu, Li; Wang, Jingshuang; Hu, Qing; Zhang, Hua; Zhang, Shangzhou; Zhou, Xin
Abstract: MoSi2 doped Yb2 Si2 O7 composites were designed to extend the lifetime of Yb2 Si2 O7 environmental barrier coatings (EBCs) via self-healing cracks during high-temperature applications. Yb2 Si2 O7 –Yb2 SiO5 –MoSi2 composites with different mass fractions were prepared by applying spark plasma sintering. X-ray diffraction results confirmed that the composites consisted of Yb2 Si2 O7, Yb2 SiO5, and MoSi2 . The thermal expansion coefficients (CTEs) of the composites increased with an increase in the MoSi2 content. The average CTE of the 15 wt% MoSi2 doped Yb2 Si2 O7 composite was 5.24 × 10 −6 K −1, indicating that it still meets the CTE requirement of EBC materials. After being pre-cracked by using the Vickers indentation technique, the samples were annealed for 0.5 h at 1100 or 1300 °C to evaluate the crack-healing ability. Microstructural studies showed that cracks in 15 wt% MoSi2 doped Yb2 Si2 O7 composites were fully healed during annealing at 1300 °C. Two mechanisms may be responsible for crack healing. First, the cracks were filled with SiO2 glass formed by MoSi2 oxidation. Second, the formed SiO2 continued to react with Yb2 SiO5 to form Yb2 Si2 O7, which can cause cracks to heal owing to volumetric expansion. The Yb2 Si2 O7 formation with smaller volume expansion is more beneficial.